Biometric Relationship Between Growth Pattern and Biological Reproduction of a Living Fossil Benthic Brachiopods (Lingula anatina Lamarck, 1801) in Aceh Northern Shore - Octavina, Chitra; Irsad, Muhammad; Al-Ihsan, Muhammad Tareqh; Niwatana, Julya; Ulfah, Maria; Nurfadillah, Nurfadillah; Agustina, Sri; Nur, Firman Muhammad; Anh, Nguyen Thi Mai (Marine Science Department Diponegoro University, 2023)
Brachiopods are a group of ancient marine invertebrates that are still found today, so they are known as